Otocephaly (Agnathia)-Situs inversus complex with bilateral absence of mandibular nerves - Kandala, Aparna VP; Nalluri, Himabindu (International Journal of Research in Medical Sciences, 2017)
Otocephaly is a rare lethal neurocristopathy of first branchial arch, characterized by agnathia (agenesis of mandible), ventro-medial displacement and midline fusion of external ears (synotia), microstomia (small mouth) and aglossia (absence of tongue) or microglossia (small tongue). This anomaly is a consequence of failure of migration of neural crest cells from hind brain which contributes to the development of maxillary and mandibular prominences of the first arch. A female fetus of 28weeks gestation, spontaneously aborted, was received for autopsy. On external examination, the fetus exhibited ventrally placed malformed ears in the neck region, agnathia, microstomia and microglossia. Internal examination revealed situs inversus totalis, atrial septal defect and bilateral absence of mandibular nerves. Our case is unique, and here rendered for publication, due to association of otocephaly with situs inversus totalis in the absence of holoprosencephaly. We discuss current perspectives, literature review and molecular mechanisms implicated in otocephaly complex patterning.